2012
DOI: 10.1371/journal.pone.0050542
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Promotes Osteogenic Differentiation of Human Dental Pulp Stem Cells In Vitro and In Vivo

Abstract: Human dental pulp is a promising alternative source of stem cells for cell-based tissue engineering in regenerative medicine, for the easily recruitment with low invasivity for the patient and for the self-renewal and differentiation potential of cells. So far, in vitro culture of mesenchymal stem cells is usually based on supplementing culture and differentiation media with foetal calf serum (FCS). FCS is known to contain a great quantity of growth factors, and thus to promote cell attachment on plastic surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 34 publications
(40 reference statements)
4
96
0
Order By: Relevance
“…In this regard, despite ongoing progress in culture media formulations that do not contain foetal serum for maintenance of DPSCs (Bonnamain et al, 2013;Eubanks et al, 2014;Jung et al, 2016;Xiao and Tsutsui, 2013), currently the addition of FBS or related agents to the culture media permits easily overcoming the issue of initial cell expansion. However, it is becoming increasingly apparent that FBS-containing media also induce differentiation of DPSCs into a default osteo/odontogenic pathway (Pisciotta et al, 2012;Yu et al, 2010) and this may not be the best choice to generate certain cell lineages, particularly neural cells, from DPSCs (Jung et al, 2016). Moreover, upon continual expansion induced by the presence of 10 % FBS, DPSC cultures also tend to generate populations of committed/differentiated cells (Mokry et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, despite ongoing progress in culture media formulations that do not contain foetal serum for maintenance of DPSCs (Bonnamain et al, 2013;Eubanks et al, 2014;Jung et al, 2016;Xiao and Tsutsui, 2013), currently the addition of FBS or related agents to the culture media permits easily overcoming the issue of initial cell expansion. However, it is becoming increasingly apparent that FBS-containing media also induce differentiation of DPSCs into a default osteo/odontogenic pathway (Pisciotta et al, 2012;Yu et al, 2010) and this may not be the best choice to generate certain cell lineages, particularly neural cells, from DPSCs (Jung et al, 2016). Moreover, upon continual expansion induced by the presence of 10 % FBS, DPSC cultures also tend to generate populations of committed/differentiated cells (Mokry et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Serum-free media have been continuously tested for stem cell culture; however, so far, the literature indicates that these media do not adequately support DPSCs proliferation and differentiation. 37,38 The growth of DPSCs with a small percentage of serum enriched with epidermal growth factor (EGF) and platelet-derived growth factor (PDGF) could represent a valid perspective. 39,40 Various human blood derivatives have been proposed as alternatives to animal serum for stem cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Various human blood derivatives have been proposed as alternatives to animal serum for stem cell culture. These include autologous or allogenic human serum, 38 human plasma, 37 and human platelet lysates and their released factors. 4 Pisciolaro and collaborators showed that autologous human serum induces higher CFUs capacity, higher degree of mineralization and less cell damage in DPSCs cells then FBS and allogenic human serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The petri dishes were then incubated at 37°C overnight. Percentage of cells expressing β-galactosidase was measured in three random fields under inverted phase contrast microscope (Nikon 80i, Japan) [20].…”
Section: Proliferation Assaymentioning
confidence: 99%